Money, Output and Stock Prices in Malaysia: An Application of the Cointegration Tests - Habibullah, Muzafar Shah; Ahmad Zubaidi, Baharumshah (1996)
The purpose of this paper is to determine whether macroeconomic variables, in particular money supply and output are important in predicting stock prices in Malaysia. Monthly data on stock price indices, money supply and output were employed in this study. The stock price indexes used in this study are Composite, Industrial, Finance, Property, Plantation and Tin. For money supply we used both M1 and M2, and output is measured by real Gross Domestic Product (GDP). Our results suggest that Malaysia’s stock market is informationally efficient with respect to money supply as well as output.